Henry Taube lecture at Brooklyn College - Taube, Henry; Brooklyn College (1986)
This talk is part of the H. Martin Friedman Lecture series at Brooklyn College, which was intended to introduce high school students to careers in chemistry. Introductions to the talk and speaker are given by Leon Gortler, chair of the Chemistry Department at Brooklyn College; Richard Pizer; and H. Martin Friedman. Henry Taube is a Canadian-born, American chemist who won the Nobel Prize for Chemistry in 1986 for his work on electron-transfer reactions in metal complexes. At the time of this lecture (1986), he was Professor of Chemistry at Stanford University. Taube discusses his career and research, starting with his teachers and mentors throughout his undergraduate and graduate studies. He also walks the audience through a few of his own chemistry experiments. This lecture was recorded on a hand-held camera by an audience member, and so the resulting video is unfortunately both dark and shaky.
Keywords: Chemistry--Study and teaching; Taube, Henry, 1915-2005; Nobel Prize winners; Lectures